Core-sheath nanostructured chitosan-based nonwovens as a potential drug delivery system for periodontitis treatment - dos Santos, Danilo M.; Chagas, Paulo A.M.; Leite, Ilaiáli S.; Inada, Natalia M.; de Annunzio, Sarah R. [UNESP]; Fontana, Carla R. [UNESP]; Campana-Filho, Sérgio P.; Correa, Daniel S. (Elsevier, 2020)
Core-sheath nanofibers were successfully prepared via coaxial electrospinning by using chitosan with well-defined structural characteristics as the shell layer and poly (vinyl alcohol) (PVA) containing tetracycline hydrochloride (TH) as the core layer. The effects of the average degree of deacetylation (DD‾) of chitosan and the post-electrospinning genipin crosslinking on physicochemical and biological properties of resulting nonwovens were evaluated. Defect-free and geometrically uniform nanofibers with diameters predominantly in the range of 100–300 nm were prepared, and transmission electron microscopy (TEM) revealed the core-sheath structures and its preservation after crosslinking. The mechanical properties, as well as the stability of nonwovens in aqueous medium, were greatly improved by genipin-crosslinking, which enabled a sustained release of TH over 14 days. Results also revealed that the release profile of TH in the presence of lysozyme was affected by the composition of the shell layer, as the TH release rate increases with decreasing of DD‾. Further in vitro antimicrobial activity demonstrated that the cross-linked nonwovens containing TH showed strong activity against bacterial strains associated with periodontal disease. Additionally, the nonwovens did not demonstrate cytotoxic toward fibroblast (HDFn) cells, hence showing their potential for applications as a novel drug delivery platform for periodontitis treatment.
Keywords: Chitosan; Coaxial electrospinning; Nanocarrier